An evaluation of the autism, emotional well-being and adolescence programme; a locally developed psychoeducation intervention for parents of young people with autism - Bishop, Tracey (2018)
Introduction: Promoting the mental health of young people is identified as a key priority in the United Kingdom (Department of Health & Department for Education, 2017). Particular groups in the population are at an increased risk of poorer mental health outcomes, for example, it is known that there is a high comorbidity between autism and mental health conditions, with an increase in prevalence around adolescence (de Bruin, Ferdinand, Meester, de Nijs & Verheij, 2006). Consequently, there has been a call for research that explores approaches to support the management of emotional issues for people with autism (Pellicano, Dinsmore & Charman, 2014). In response, this study presents the first evaluation of the Autism, Emotional Well-being and Adolescence (AEWA) psychoeducation programme for families of children with autism. The programme aims to develop parents’ understanding of emotional wellbeing and how to promote it, with a particular focus on adolescence.